Η επίδραση της αντικατάστασης του χλωριούχου νατρίου στις φυσικοχημικές, μικροβιολογικές και οργανοληπτικές ιδιότητες του τυρού χαλλούμι - Μιχαήλ, Μιχαήλ (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
The overall objective of this study was to investigate the effect of Salona salt substitution on the chemical, physical, microbiological and organoleptic properties of Halloumi cheese. The test samples had similar chemical composition, texture profiles and microstructure compared to controls during the same storage and maturation period. At the same time Salona salt did not exhibit less antimicrobial activity than the conventional, hence preserving the product for the same amount of time. Additionally, the texture analyzer results (hardness and chewiness) did not differ between the Salona and the control. However, the untrained consumer test (triangle test) showed that there was a significant difference between the cheeses made from the two types of salt. The main differences between the two samples were the highest hardness, consistency and sharpness, with low cheese intensity in terms of moisture content. Further research is therefore needed on the effects of Salona salt and on the use of other additives that could help to improve consumer acceptance.
Keywords: Haloumi; Salona salt; Texture profiles; Microbiological properties; Χαλλούμι; Αλάτι Salona; Προφίλ υφής; Μικροβιολογικές ιδιότητες